(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Affirmation of Freedom and Christian Education in the Era of Digitalization by Resorting to Petre Dulfu’s Biblically Inspired LyricThis article aims to highlight the importance of bringing to light the old texts of some writers, trying to educate readers through digital means and marking the perennial of these teachings. One of the most writers of the late nineteenth and early twentieth centuries was Petre Dulfu, a petagogue influenced by the educational framework given by Spiru Haret’s reform, who wanted to make known not only the folkloric vein, but also the scriptural one so that people know the word of God. The affirmation of the author’s freedom can also be seen in the volume Jesus the Saviour, in which he resorts to transforming the text of the New Testament into verse. Although the texts of the writer born in Tohat have been forgotten, we have the duty to make them known through modern means so that these creations speak and transmit teachings to those of today.